Analysis and experiment of a VTOL flapping wing rotor micro aircraft - Pan, Yingjun (Cranfield University, 2023)
This thesis presents an in-depth study of the aerodynamic and structural analysis of a novel bio-inspired flapping wing rotor (FWR) micro aerial vehicle (MAV) capable of vertical take-off and landing. The FWR is characterized by a combination of active flapping motion with passive rotation of the wings in an asymmetric installation to produce a significantly higher lift coefficient than traditional flapping wings. This research is aimed at further enhancing the FWR MAV’s efficiency and aerodynamic performance with flight capability and stability. This is approached by improving the FWR kinematics of motion and mechanism through analytical, numerical simulation, and experimental methods. In the first step, an efficient wing rotation method that allowed a small angle of attack in the downstroke and a larger one in the upstroke was considered. A novel Passive Pitching Angle Variation (PPAV) device, replacing traditional active rotation, was developed and integrated into the flapping mechanism. Using a high-speed camera and a load cell device for experiments, the PPAV-integrated FWR demonstrated a significant increase in aerodynamic efficiency compared to its constant pitch angle counterpart. In the second step, the study focused on enhancing FWR-MAV power efficiency by integrating springs into the mechanism, thereby reducing input power due to the counterbalance between elastic and inertia forces. Numerical analysis and experimentation with an FWR test model were conducted to simulate and measure the resultant kinematics of motion and forces. Specific emphasis was placed on the influence of spring stiffness on the FWR’s aerodynamic and power efficiency. This led to the development of a PPAV-integrated FWR model capable of remote-controlled vertical take-off and hovering. In the third step, the study explored wing flexibility’s impact on FWR’s unsteady aerodynamics using Fluid-Structure Interaction (FSI) analysis and experiments. A novel dragonfly-like wing with a curved sweep-back wingtip demonstrated aerodynamic benefits. The study elucidates the mechanism of wing bending deformation linked to vortex variation, implying that optimal spanwise variable stiffness can enhance lift and power efficiency. Employing flexible wings, the FWR model’s lift significantly increased from 25 g to 51 g, highlighting enhanced efficiency and payload capacity. The study finally explored the FWR-MAV's flight performance and efficiency, including VTOL and forward flight. It proposed a transformable MAV concept from VTOL FWR mode to a bird-like flapping-wing mode in forward flight. A test model was built to validate the transformation concept. Using MSC.ADAMS/Simulink co- simulations and a quasi-steady aerodynamic method, the flights of the FWR model in both flight modes were simulated and stability was demonstrated.
Whidborne, James F. - Associate Supervisor
Keywords: Flapping Wing Rotor; Passive Pitching Angle Variation; Elastic Mechanism; Aerodynamic Performance; Power Efficiency; Flight Simulation